Critical Infrastructure Resilience in the PRECINCT Project - Connolly, Lorcan; Schauer, Stefan; Egger, Manuel; König, Sandra; ICASP14; Sheils, Emma; OConnor, Alan (My University, 2023)
The PRECINCT project brings together Critical Infrastructure owners and authorities from four Living Lab cities throughout Europe. These Living Labs then operate as a coordinated precinct responding to the various cyber-physical threats to which they are exposed. This paper describes the combined cascading effects / interdependency tool developed in the project to calculate the resilience of interconnected infrastructures. Serious Game play is simulated through stakeholder workshops which illustrate how the interdependency graph can be deployed for both training and as a tool to gather further information on threats and interconnections in the infrastructure.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED